Effect of annealing temperature on the value of contact resistance of ohmic contacts to InP - Novitskyi, S. V. (Technology and design in electronic equipment, 2012)
It is experimentally confirmed that the temperature dependence of specific contact resistance of ohmic contacts Au–TiB2–Ge–Au–n–n+–n++-InP is described with the current transport model with a high density of dislocations in the contact region of the semiconductor. The samples used in the experiment were obtained at different annealing temperatures.